1999
DOI: 10.1289/ehp.99107117
|View full text |Cite
|
Sign up to set email alerts
|

Acute gastrointestinal effects of graded levels of copper in drinking water.

Abstract: The objectiv of this study was to determine the acute gastrointestinal effects caused by the consumption ofdrinking water coning graded levels ofadded copper. Sixty healy, adult women were randomly assigned to receive copper [Cu(II)] at four concentrations in their drinking water following a latin-square design. Each group (n -15) received tap water with no added copper, 1, 3, and 5 mg Cull of added copper sulfte for a 2-week study period, followed by 1 week of standard tap water. The subjecs recorded their wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…High levels of copper are associated with nausea, abdominal pain, or vomiting in humans (Pizarro et al, 1999). Concentrations of copper in groundwater (0.0015 mg/l) were greater than that of surface water (0.0020 mg/l).…”
Section: Arsenic Cadmium and Mercurymentioning
confidence: 91%
“…High levels of copper are associated with nausea, abdominal pain, or vomiting in humans (Pizarro et al, 1999). Concentrations of copper in groundwater (0.0015 mg/l) were greater than that of surface water (0.0020 mg/l).…”
Section: Arsenic Cadmium and Mercurymentioning
confidence: 91%
“…A main limitation of this study is the lack of control of the exact timing of exposure and appearance of symptoms. This was indeed performed in the above-mentioned clinical trials that led to the dose–response curve (Araya et al 2001; Gotteland et al 2001; Olivares et al 2001; Pizarro et al 1999). Instead, in the present study the main objective was to assess to what extent this dose–response curve is applicable when individuals are exposed to Cu in a more realistic fashion.…”
Section: Discussionmentioning
confidence: 98%
“…Vomiting was observed in 11.5% of the study subjects and was first reported at 6 mg/L, showing a 2-fold increase when the Cu concentration reached 10–12 mg Cu/L. Diarrhea and abdominal cramps were rare within the range of concentrations studied (Araya et al 2001; Gotteland et al 2001; Olivares et al 2001; Pizarro et al 1999). Using these dose–response curves and the 95% confidence intervals (CI), the Cu concentration at which 5% of the population would experience nausea was 2.0 mg Cu/L for the crude initial response and 4.2 mg Cu/L for the nausea response confirmed by repeat testing (Olivares et al 2001).…”
mentioning
confidence: 81%
See 2 more Smart Citations